2019
DOI: 10.1200/jco.2019.37.15_suppl.2609
|View full text |Cite
|
Sign up to set email alerts
|

Phase I safety and pharmacokinetic study of KN035, the first subcutaneously administered, novel fusion anti-PD-L1 antibody in Japanese patients with advanced solid tumors.

Abstract: 2609 Background: KN035 is a novel fusion protein of humanized anti-PD-L1 single domain antibody and human IgG1 Fc, formulated for subcutaneous (SC) injection. A phase I safety and pharmacokinetic (PK) study was conducted in Japanese patients. Methods: Patients with advanced solid tumors were treated with KN035 SC once every-7-days (QW) or once every-14-days (Q2W) schedules with the dose limiting toxicities (DLT) evaluation period of 28 days. For the QW schedule, the starting dose was 1 mg/kg (n=3) with escala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The full therapeutic dose of envafolimab (150 mg) can be delivered as a single 0.75-ml subcutaneous injection in under 30 s due to the high solubility of the fusion protein (200 mg/mL). Across phase 1 dose-escalation studies in advanced cancers, confirmed response rates ranged from 14 to 18%, and no infusion reactions and only two grade 3 treatment-related adverse events (AEs) were reported [ 20 22 ]. Pharmacokinetic analyses of envafolimab monotherapy showed that 150 mg once weekly would provide a sufficient exposure in cancer patients [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The full therapeutic dose of envafolimab (150 mg) can be delivered as a single 0.75-ml subcutaneous injection in under 30 s due to the high solubility of the fusion protein (200 mg/mL). Across phase 1 dose-escalation studies in advanced cancers, confirmed response rates ranged from 14 to 18%, and no infusion reactions and only two grade 3 treatment-related adverse events (AEs) were reported [ 20 22 ]. Pharmacokinetic analyses of envafolimab monotherapy showed that 150 mg once weekly would provide a sufficient exposure in cancer patients [ 23 ].…”
Section: Introductionmentioning
confidence: 99%